Distribution of the Condylion-Gonion-Menton (CoGoMe^) Angle in a Population of Patients from Southern Italy - Vicenzo D'Antò; Ada Carolina Pango Madariaga; Roberto Rongo; Rosaria Bucci; Vittorio Simeon; Lorenzo Franchi; Rosa Valletta (MDPI AG, 2019)
The condylion-gonion-menton angle (CoGoMe^) is commonly used as a pre-treatment indicator of responsiveness in Class II patients treated with functional appliances. The distribution of this angle in the Caucasian population is still unknown. This study aimed to determine the distribution of the CoGoMe^ and its relationship with age, sagittal jaw relationship (ANPg^), and mandibular inclination (SN^GoGn) in patients from Southern Italy. The sample included 290 subjects (median14 years of age; Interquartile range, IQR, 12−17) with lateral cephalograms taken before the orthodontic treatment. The distribution of the CoGoMe^ was assessed with the Shapiro−Wilk test, and the differences according to the ANPg^ and the SN^GoGn were estimated using one-way ANOVA. Linear regression analysis was performed to evaluate how the CoGoMe^ varied according to age. The statistical significance was set at P < 0.05. The results showed that the CoGoMe^ was normally distributed (P = 0.290) with a mean value of 127.2° ± 7.7°. The distribution of the CoGoMe^ in groups with different SN^GoGn angles was significantly different (P < 0.001). These angles showed a positive association (Beta coefficient B = 0.6; 95% CI: 0.51, 0.67; P < 0.001). In growing patients, the CoGoMe^ decreased every year by 0.6° (B = −0.6; 95% CI: −1.05, −0.12; P = 0.014). In conclusion, the CoGoMe^ was associated with mandibular inclination and could be considered to be a predictor of vertical growth patterns.